Intercultural Communication in Javanese–Madurese Marriages: A Descriptive Qualitative Study - M. Zidan Arifaini (Communigate, 2025)
This qualitative descriptive study explores intercultural communication in marriages between Javanese and Madurese ethnic groups in Indonesia. The research examines cultural interactions, communication patterns, and adaptation strategies employed during the marriage process, from courtship through ceremonial traditions. Analysis reveals how these distinct cultural groups navigate differences in language, customs, family systems, and religious practices to establish mutual understanding and harmonious relationships. The study identifies key challenges, conflict resolution approaches, and cultural negotiation strategies utilized by couples. Findings highlight the dynamic process of cultural integration where elements from both Javanese and Madurese traditions are preserved, adapted, or blended to create new shared meanings and practices within these intercultural marriages. This research contributes to understanding intercultural communication dynamics within Indonesia's diverse ethnic landscape and offers insights for supporting successful cross-cultural relationships.